THE LEAN SIX SIGMA IN A PUBLIC HOSPITAL - tadlaoui, kenza (Journal of Applied Engineering Science, 2018)
The hospital can be likened to an industrial enterprise with a high level of security expected. Indeed, the patient has particularities: it is a living being brought to the hospital in an uncontrolled manner and difficult to regulate or anticipate accurately. In addition, the constraint in the public hospital is financial: It is to treat a maximum of patients, the best possible, with limited financial resources. Despite this constraint, patient demands are high in terms of quality of treatment and medical innovations. Hence the interest of using the methods used in the industrial management of high security environments namely Lean management to adequately meet the constraints of economic and societal efficiency, flexibility and security imposed by the hospital stakeholders. In this article, we will try to define the concept of Lean six sigma in care institutions, then we will describe the methodology adopted that of the DMAIC method and in the end to implement the first 3 steps of this method. in a public hospital.